Analisis work engagement karyawan frontline high-contact dan low-contact di industri jasa - Sucipto Asan; Juanna Judith Huliselan (Jurnal Manajemen Maranatha, 2020)
Work engagement (positive working mind and emotion) in frontline employees (FLEs) plays an important role that will affect the capability of the organization in serving its customer. The goal of this research is to examine whether there were differences in the influence of service climate, job satisfaction, and affective commitment toward work engagement in high-contact and low-contact frontline employees in Jakarta and Tangerang; and whether there were influences of work engagement toward adaptability behavior as well as career commitment among high-contact and low-contact frontline employees. Questionnaire is administered to 200 FLEs from multiple high and low contact service industries in Jakarta and Tangerang. Structural Equation Modeling-Partial Least Square (SEM-PLS) is used to test hypotheses. The author found there were almost no differences among high-contact and low-contact frontline employees except on the job satisfaction, where there was no significant influence toward work engagement in frontline low-contact employee which was in contrast with the frontline high-contact employee. This research will enrich the discourse on the relationship between job satisfaction and work engagement. This finding provides empirical evidence on a limited scale that in certain segmentation, especially for low-contact workers, job satisfaction did not have a positive influence on work engagement.